2023
DOI: 10.3390/nano13061103
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectromechanical Temperature Sensor Based on Piezoresistive Properties of Suspended Graphene Film

Abstract: The substrate impurities scattering will lead to unstable temperature-sensitive behavior and poor linearity in graphene temperature sensors. And this can be weakened by suspending the graphene structure. Herein, we report a graphene temperature sensing structure, with suspended graphene membranes fabricated on the cavity and non-cavity SiO2/Si substrate, using monolayer, few-layer, and multilayer graphene. The results show that the sensor provides direct electrical readout from temperature to resistance transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…(a) 石墨烯柔性温度触觉传感电子皮肤的结构图. (b) 石墨烯柔性温度触觉传感电子皮肤温度检测 机理 Figure 5 Thermoresistive flexible tactile electronic skin for temperature sensing [116] . (a) Basic structure of graphene-based thermoresistive flexible tactile electronic skin for temperature sensing.…”
Section: 其中 垂直接触分离模式需要两个背面附有电极层的mentioning
confidence: 99%
“…(a) 石墨烯柔性温度触觉传感电子皮肤的结构图. (b) 石墨烯柔性温度触觉传感电子皮肤温度检测 机理 Figure 5 Thermoresistive flexible tactile electronic skin for temperature sensing [116] . (a) Basic structure of graphene-based thermoresistive flexible tactile electronic skin for temperature sensing.…”
Section: 其中 垂直接触分离模式需要两个背面附有电极层的mentioning
confidence: 99%
“…One prominent application lies in electronic devices, including FETs [41,60,61], logic gates [62,63], photodetectors [64][65][66][67][68], resonators [69][70][71][72], and sensors [73][74][75][76][77][78]. For instance, Han et al demonstrated that incorporating piezoresistive properties in suspended graphene membranes enhances sensitivity and expands the temperature-sensing range in nanoelectromechanical system (NEMS) temperature sensors [129]. In the case of pressure sensors, the working mechanism relies on the local compression deformation of the suspended graphene lattice.…”
Section: Applications Of Suspended 2d Materialsmentioning
confidence: 99%